The irreversible relaxation of inflation - Robert Alicki; Gabriela Barenboim; Alejandro Jenkins (Physics Letters B)
Based on the results of a previous analysis of the Markovian master equation for the irreversible evolution of an open system embedded in de Sitter space [7], we include in the cosmological Friedmann equations a contribution from the presence of a physical bath at temperature TdS=h/2π, where h is the Hubble parameter. We show that this provides a mechanism for the irreversible relaxation of the cosmological constant and a graceful exit to inflation, without need for subsequent reheating. Thermal particle production during inflation gives adiabatic, Gaussian, and approximately scale-invariant cosmological perturbations. We thus obtain the main features of inflation without any inflaton potential. To clarify the thermodynamic interpretation of these results, we consider the analogy of this irreversible relaxation to superfluorescence in quantum optics.